2023
DOI: 10.3390/biomedicines11030744
|View full text |Cite
|
Sign up to set email alerts
|

Application of Biodegradable Magnesium Membrane Shield Technique for Immediate Dentoalveolar Bone Regeneration

Abstract: For the first time, the clinical application of the first CE registered magnesium membrane is reported. Due to the material characteristics of magnesium metal, new treatment methodologies become possible. This has led to the development of a new technique: the magnesium membrane shield technique, used to rebuild the buccal or palatal walls of compromised extraction sockets. Four clinical cases are reported, demonstrating the handling options of this new technique for providing a successful regenerative outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…More recently, Elad et al utilized the resorbable magnesium barrier to establish a lost buccal bone wall in conjunction with an immediate implant placement protocol. In this case report none of the patients presented severe postoperative complications [13].…”
Section: Introductionmentioning
confidence: 51%
“…More recently, Elad et al utilized the resorbable magnesium barrier to establish a lost buccal bone wall in conjunction with an immediate implant placement protocol. In this case report none of the patients presented severe postoperative complications [13].…”
Section: Introductionmentioning
confidence: 51%
“…Magnesium membranes provide improved properties, such as strength and dimensional stability, during wound healing without the need to reopen the surgical site for their removal [ 15 ]. The aforementioned mechanical properties allowed Elad et al to develop a new technique, the magnesium membrane shield technique, which was described and applied to four of their clinical cases [ 20 ]. The handling of magnesium membrane is different from that of collagen.…”
Section: Discussionmentioning
confidence: 99%
“…Amberg et al demonstrated the successful adhesion of human gingival fibroblasts to the membrane surface and showed how the migration rate changed as a function of Mg 2+ and Ca 2+ concentrations [ 23 , 24 ]. As mentioned earlier, Elad et al reported the first use of the pure magnesium membrane in a completely new technique that was not previously possible with a resorbable membrane due to the lack of mechanical stability in the alternative options [ 20 ].…”
Section: Literature Search and Review Of Current Knowledge On Magnesi...mentioning
confidence: 99%
See 1 more Smart Citation
“…The magnesium-based GBR membrane has a similar barrier function to the collagen membranes but exerts additional space maintenance properties comparable to titanium-based products [ 28 , 29 ]. It has already been shown that the membrane provides a good bone tissue regeneration and soft tissue healing in combination with an allograft biomaterial [ 33 , 34 ], and a recent review highlighted the many benefits of magnesium metal membranes. The biocompatibility, inflammatory response, and non-toxicity of the magnesium membrane were recently reported [ 28 ].…”
Section: Introductionmentioning
confidence: 99%